Relationship Between the Leadership Styles of Nursing Managers and Teamwork of Nurses in University Hospitals of Mashhad and Zahedan, Iran - Sajad Faal Sanati; Eshagh Barfar; Abolfazl Payandeh; Mohammad Khammarnia (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Policymakers can enhance personnel performance and consequently, improve the quality of healthcare by evaluation of suitable leadership styles for health organizations and establishment of effective team groups. This study aimed to determine the relationship between the leadership styles of nursing managers and the teamwork of nurses. Methods: This descriptive-analytic study was conducted among 500 nurses working in eight selected university hospitals in Mashhad and Zahedan, Iran (2022). Data were collected using two standard questionnaires on leadership styles and teamwork through interviews. Descriptive statistical methods, such as the mean and standard deviation, were employed to determine leadership style and teamwork scores. Additionally, Pearson's and Spearman's correlation coefficients were used to investigate the relationship between these two variables. Results: The dominant leadership style among the participants was transformational leadership (37.6%). The overall mean teamwork score was 3.66±0.48, with 91.8% of nurses scoring teamwork 3 or higher. Transformational and passive leadership styles exhibited the highest and lowest relationships with teamwork, respectively (P<0.05). Additionally, the mean teamwork score among nurses with managers exhibiting a transformational leadership style was higher, compared to other styles (P<0.05). Conclusion: Managers and executive supervisors can positively impact teamwork and consequently, the performance indicators of their unit by adopting a transformational leadership style and enhancing their leadership knowledge. To achieve this goal, it is suggested to conduct in-service training courses. Additionally, selecting supervisors of centers who promote teamwork and designing a mechanism to collect feedback from hospital personnel regarding the leadership style of their direct managers are recommended.